Selección e instalación de vapor para una fábrica de yogurt y de crema de leche - Díaz V., Dennys (2010)
Steam is one of the essential elements in the process of preparing the yogurt and cream, the objective is to precisely calculate a steam system according to the requirements of the product to be processed. For this project became a collection of statistical data on annual production and consumption of yogurt and cream in Ecuador with its future projections and thus determined the amount of product to process. Then we determined the total steam requirements are projected for the future and it was selected according to the type of steam generator and control devices to be used for the production of yogurt and cream. Also analyzed and estimated the water supply system and their treatment also analyzed the fuel system. Then we calculated and designed for steam pipes and condensate return and selection of steam traps.